ARI updates 2016: Higher Institution Centre of Excellence (HiCoE) - UiTM, Accounting Research Institute (Accounting Research Institute (ARI), 2016)
The Accounting Research Institute (ARI) was initially formed as a special interest group in 2002. Its role was to pave the pathway for systematic and robust research in accounting specifically in areas such as the practice and theory of financial accounting, financial criminology, corporate governance, management accounting, financial reporting, public sector accounting, taxation and accounting information system. Over the years, ARI has advanced from being a special interest group and to becoming a research centre, and now a research institute. In November 2009, the Ministry of Higher Education recognized ARI as the Higher Institution Centre of Excellence (HiCoE). ARI currently has eight (8) centres of excellence under its wings.